1981
DOI: 10.1111/j.1502-3885.1981.tb00467.x
|View full text |Cite
|
Sign up to set email alerts
|

A marine seismic study of late Quaternary sedimentaion and inferred glacier fluctuations along western Inverness‐shire, Scotland

Abstract: A sparker survey was undertaken of the sea area inshore of the peninsula of sleat and the islands of Eigg and Muck in Western Scotland. This revealed major submarine moraines across the mouths of Loch Nevis and Loch Ailort, which help define the margin of a major glacier readvance phase, presumed to be equivalent to the late‐glacial Loch Lomond Readvance. Formation names are suggested for the seismic para‐stratigraphy. West of the moraines, there is a till (Minch Para‐formation) resting on bedrock, overlain by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 6 publications
3
15
0
2
Order By: Relevance
“…Despite their obvious importance as a connection between the terrestrial and marine glacial records, Scotland's fjords have received relatively little attention in terms of their glacial history (Boulton et al, 1981;Dix and Duck, 2000;Howe et al, 2001Howe et al, , 2002Nørgaard-Pedersen et al, 2006;Stoker et al, 2006). This is surprising considering that fjords commonly act as effective sediment traps during deglaciation, and have the potential to provide a highresolution sediment record that reflects both local terrestrial and marine processes (Syvitski and Shaw, 1995).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Despite their obvious importance as a connection between the terrestrial and marine glacial records, Scotland's fjords have received relatively little attention in terms of their glacial history (Boulton et al, 1981;Dix and Duck, 2000;Howe et al, 2001Howe et al, , 2002Nørgaard-Pedersen et al, 2006;Stoker et al, 2006). This is surprising considering that fjords commonly act as effective sediment traps during deglaciation, and have the potential to provide a highresolution sediment record that reflects both local terrestrial and marine processes (Syvitski and Shaw, 1995).…”
Section: Introductionmentioning
confidence: 93%
“…The longest fjords (or sea lochs) range from 10 to 30 km, and commonly exceed 150 m at their maximum water depth. Maximum-recorded sediment infill (sea bed-rockhead) is between 50 and 70 m in Loch Nevis (Boulton et al, 1981) and Loch Etive , and locally up to 100 m in Loch Broom (Stoker et al, 2006;Stoker and Bradwell, In press). It has recently been proposed that the major fjords in NW Scotland most probably formed tributaries that fed the Minch palaeo-ice stream; a shelf-crossing ice-stream that dominated the northwestern sector of the British Ice Sheet (BIS) (Stoker and Bradwell, 2005;Bradwell et al, 2007Bradwell et al, , 2008c (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This evidence leads us to infer that the 293 streamlined landforms observed at seabed are formed of subglacial sediments (where not eroded 294 into bedrock) equivalent to the Hebrides Formation within the pre-existing regional seismo-295 stratigraphic framework. Underlying the Barra and Jura Formations, the Hebrides Formation 296 (termed 'Minch Formation' by Boulton et al (1981)) is a discontinuous coarse-grained diamict 297 interpreted as subglacial till (Davis et al, 1984). Where present at seabed this diamict is likely very 298 thin across the study area.…”
mentioning
confidence: 99%
“…This absence of drift has been attributed to very active glaciers flowing through these valleys and calving in the sea lochs, removing deposits from the valley sides (Bennett, 1991). Seismic surveying of these sea lochs revealed the presence of large moraine ridges across the mouths of Loch Nevis and Loch Ailort, which were believed to date to the LLS and correlated to the onshore mounds mapped at the head of Loch Morar (Boulton et al, 1981). McIntyre et al (2011) identified moraine ridges in Loch Hourn (Fig.…”
Section: Torridon To Loch Linnhementioning
confidence: 97%